Construction of Concrete Wall with Resistance to Explosions- Aview - Shaik Himam Saheb; Chandrashekhar; B. Sri Maniteja Goud (Global Journals of Research in Engineering, 2022)
The research was to give the people a great protect against the explosions by using Fiber #x2013; reinforced concrete. The Fiber #x2013; reinforced concrete is very difficult to be used in the actual Construction as the Fiber can#x2019;t be mixed up with the ready mixed concrete system. The Fiber has a high resistance against the blasts and also needed a huge load of fiber. The required amount of fiber can result in reduced in practicable and lacking quantity of fiber. It#x2019;s been very tough to put fiber #x2013; reinforced concrete on site Placing with ready mixed concrete system plant for mixing and placing. Thus, it has analysed properties of Steel and polymeric fiber to increase practicable and shaking in mixer. The beginning experimental test mixing fiber reinforced concrete has been tested in the actual field Construction of chemical plant. As the result from the test, it is expected to present to the combined fiber for required mechanical performance with unfavourable effect on practicable of the Mixture.